Spark - Durst, Sarah Beth (Clarion Books, 2019)
In the land of Alorria, where mystical beasts and their human guardians create perfect weather every day, twelve-year-old Mina longs to get a storm beast of her very own--she is shy, however, and so it is a mystery to everyone when Pixit, a lightning beast of chaos and fire, bonds with Mina. Now Mina and Pixit are enrolled in lightning school to train for their duties, but when Mina learns the dark truth behind Alorria's idyllic weather and its terrible cost, her world is shattered.